2015
DOI: 10.1039/c5cp02345a
|View full text |Cite
|
Sign up to set email alerts
|

Molecular diffusion and dc conductivity perfectly correlated with molecular rotational dynamics in a plastic crystalline electrolyte

Abstract: We probe the ion conduction and the molecular dynamics in a pure and lithium-salt doped dinitrile molecular plastic crystal. While the diffusion of the Li + ions is decoupled from the molecular reorientational dynamics, in the undoped plastic crystal the temperature dependence of the mobility of dinitrile ions and thus of the conductivity is virtually identical to that of on-site molecular rotations. The undoped material is found to obey the Walden and Stokes-Einstein rules typical of ideal liquid electrolytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 42 publications
(68 reference statements)
6
33
0
Order By: Relevance
“…Such a non-Arrhenius temperature dependence of the conductivity is typical for ionic conduction in glasslike materials if there is some coupling of the ionic mobility to the glassy -relaxation dynamics. 6,12,18,56,57 Non-Arrhenius behavior of the latter is a hallmark feature of glassforming liquids 50,51,58 but is also found for PCs. However, there the deviations usually are weaker, 7,19,56,59 in accord with the relatively moderate deviations from linear behavior in Fig.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Such a non-Arrhenius temperature dependence of the conductivity is typical for ionic conduction in glasslike materials if there is some coupling of the ionic mobility to the glassy -relaxation dynamics. 6,12,18,56,57 Non-Arrhenius behavior of the latter is a hallmark feature of glassforming liquids 50,51,58 but is also found for PCs. However, there the deviations usually are weaker, 7,19,56,59 in accord with the relatively moderate deviations from linear behavior in Fig.…”
Section: Resultsmentioning
confidence: 98%
“…10,11,12 The most prominent of these materials is succinonitrile (SN), whose ionic conductivity for different ion species and concentrations was thoroughly investigated by Alarco et al 11 More recently, the fundamental importance of the composition of the plastic-crystalline matrix for the ionic mobility was revealed: It was shown that mixtures of SN with the related molecular compound glutaronitrile (GN) have strongly enhanced ionic conductivity. 12,17,18 The mixtures exhibit stable PC phases between 15 and 70 mol% of GN 19,20 and their conductivity drastically increases with increasing amounts of GN. 12 This conductivity enhancement is accompanied by a successively stronger coupling of molecular reorientation and ionic translation.…”
Section: Introductionmentioning
confidence: 99%
“…However, the fact that the activation energy increases with increasing temperature suggests that the conduction is still electronic in nature above 215 K, since the opposite behavior (decrease of E a with increasing temperature) is usually observed in the case of ionic conduction [20,43]. On the other hand, the fact that a new dominant charge conduction mechanism starts being effective only above the threshold temperature of 215 K is reminiscent of the behavior of another fullerene derivative, namely the polymeric salt Li 4 C 60 [44,45].…”
Section: R [Nm]mentioning
confidence: 93%
“…Dielectric spectroscopy, closely related to impedance spectroscopy, is a versatile technique that allows studying in a single experiment both the conduction properties and the molecular dynamics of a sample [20]. In this contribution we employ dielectric spectroscopy to investigate electrical conduction and dipolar molecular dynamics in the solid phase of the halofullerene C 60 Br 6 derivative.…”
Section: Introductionmentioning
confidence: 99%
“…10 OD solids exhibit many of the phenomenological features of glass formers, displaying in particular a cooperative rotational motion, called α relaxation, that undergoes a continuous, dramatic slow-down upon cooling, 11,12 leading in some cases to a glass-like transition associated with rotational freezing. 13,14 Contrary to structural glasses, which do not exhibit any long-range order, OD phases are characterized by a translationally ordered structure and can therefore be more thoroughly characterized with the help of methods that exploit the translational symmetry such as Bragg diffraction, lattice models, or solid-state NMR spectroscopy. Even more importantly, since as mentioned OD phases are generally formed by molecular species with a simple structure and low number of atoms, solid-state molecular simulations are computationally affordable and can be performed with a relatively large number of molecules.…”
Section: Introductionmentioning
confidence: 99%